The Representation of Objects in Apraxia: From Action Execution to Error Awareness - Canzano, Loredana; Scandola, Michele; Gobbetto, Valeria; Moretto, Giuseppe; D’Imperio, Daniela; Moro, Valentina (Frontiers in Human Neuroscience, 2016)
Apraxia is a well-known syndrome characterized by the sufferer’s inability to perform routine gestures. In an attempt to understand the syndrome better, various different theories have been developed and a number of classifications of different subtypes have been proposed. In this paper review, we will address these theories with a specific focus on how the use of objects helps us to better understand upper limb apraxia. With this aim, we will consider transitive versus intransitive action dissociation as well as less frequent types of apraxia involving objects, i.e. constructive apraxia and magnetic apraxia. Pantomime and the imitation of objects in use are also considered with a view to dissociating the various different components involved in upper limb apraxia. Finally, we discuss the evidence relating to action recognition and awareness of errors in the execution of actions. Various different components concerning the use of objects emerge from our analysis and the results show that knowledge of an object and sensory-motor representations are supported by other functions such as spatial and body representations, executive functions and monitoring systems.